Sinergi Pesantren Dan Perguruan Tinggi ( Studi Pengembangan Kurikulum Ma’had Sunan Ampel Al-Ali Malang) - Bakar, Abu (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Pesantren education model developed with the name and style varied, in the development of pesantren faced with two problems: on the one hand schools should organize themselves in accordance with the demands of the times without having to leave the pesantren tradition itself, on theother hand how to form the product of competent scholars in the Islamic religion in order to preserve the identity of the Islamic boarding school in contributing in planting akhlaqul karimah.In the present study found some of the fidings including the following: fist, planning a curriculum that begins with the formulation of curriculum objectives, the foundation in curriculum planning and the formulation of curriculum content; both, in the implementation of the curriculum, thediscovery of the policies in developed curriculum, the ability of teachers in implementing curriculum and the constraints encountered in developing the curriculum, and the third, evaluation, the evaluation found the use of summative evaluation with a closed approach.Keywords: Islamic School, University.